KOMPETENSI, PROFESIONALISME KERJA DAN KINERJA KARYAWAN - Jefri Iswanto (JIANA ( Jurnal Ilmu Administrasi Negara ), 2017)
Abstract: Competence, professionalism Employment and Employee Performance. Theresearch objective was to determine the effect of competence and professionalism of the workto employees performance at BPJS Employment Pekanbaru. The study population was allemployees BPJS and samples taken as many as 50 people with simple random sampling technique.Data collection techniques were questionnaires, interviews and observation. Analysis of datausing multiple linear regression. The result showed that the competence and professionalismsimultaneously significant effect on employee performance with the correlation (r) 0.760. R 0.760meaningful contribution with competence and professionalism in the performance of employeesis only 57.8%, while the remaining 42.2% is determined by other factors.